After unity : reconfiguring German identities - Jarausch, Konrad Hugo (Modern German studies (Providence, R.I.) ;, 1997)
After the fall of the Wall revealed the precariousness of GDR loyalties and precipitated the rush to unity, the enlarged Federal Republic can no longer be considered a provisional construct; it is forced to rethink its own role and purpose as a nation-state. In order to probe this new uncertainty and to explore the consequences of unification for German politics, history and culture, political scientists, historians and literary scholars have come together in this volume to focus on the main issues of the current debate such as the shadow of the Nazi past, the threat of xenophobia, new regional tensions, persistent problems of gender relations, and the future shape of Europe. From these interdisciplinary essays a complex picture of competing and complementary identities emerges that challenges traditional and simplistic Anglo-American stereotypes and offers compelling evidence of a self-critical spirit and the democratic nature of the political culture of the new Germany.